Sabzawārī's Sharḥ al-Manẓūmah as an Intellectual Work in Philosophy - Febrian, Rizky (Universitas Islam Negeri Raden Intan Lampung, 2023)
Abstract;Mullā Hādī Sabzawārī (d.1873) was best known for his revival of the ideas of Mulla Ṣadrā (d.1640 A.C.) and his commentary on Ṣadrā’s al-Asfār and al-Shawāhid al-Rubūbiyyah. However, the elaboration of his philosophy could more be traced out by referring to his magnum opus, Sharḥ al-Manẓūmah. The book is the most popular textbook of scholastic philosophy which has been, and even today is being read and studied by students of philosophy in almost all the traditional religious schools (madāris) in Iran. This article is a discourse on the book Sharḥ al-Manẓūmah as a scholarly work in the field of philosophy. This study is based on a qualitative method in which content analysis is utilized in describing the work of. Sabzawārī. This results in special characteristics of the book including its style and structure of writing, the content of the discussion, its influence on the other scholars, and its appropriateness as a reference work in the field of philosophy.Keywords:Metaphysics; Philosophy; Sabzawārī; Sharḥ al-manẓūmah; the Concept of Existence. Abstrak;Mullā Hādī Sabzawārī (w.1873) dikenal atas usahanya untuk membangkitkan kembali idea-idea Mullā Ṣadrā (w.1640) dan syarahan beliau terhadap kitab al-Aṣfār dan al-Shawāhid al-Rubūbiyyah-nya Ṣadrā. Akan tetapi, penjelasan filsafatnya dapat lebih dijejaki dengan merujuk kepada karya agungnya, Sharḥ al-Manẓūmah. Karya ini adalah buku teks filsafat skolastik yang paling popular yang pernah, dan bahkan hingga hari ini masih dibaca dan dikaji oleh para pelajar filsafat di hampir semua sekolah agama tradisional (madāris) di Iran. Makalah ini akan membicarakan kitab Sharḥ al-Manẓūmah sebagai karya ilmiah dalam bidang filsafat. Kajian ini berasaskan kajian kualitatif iaitu berbentuk analisis terhadap karya Sabzawārī tersebut. Sehingga menghasilkan ciri-ciri keistimewaan kitab yang merangkumi gaya dan struktur penulisan, kandungan perbincangan, pengaruh kitab kepada para ulama dan kewajarannya dijadikan sebagai karya rujukan dalam bidang filsafat.Kata Kunci: Filsafat; Konsep Wujud; Metafizik; Sabzawārī; Sharḥ al-manẓūmah.